2022
DOI: 10.1007/s11102-022-01218-y
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Withdrawal Syndrome following treatment of endogenous Cushing Syndrome

Abstract: Purpose: Literature regarding endogenous Cushing syndrome (CS) largely focuses on the challenges of diagnosis, subtyping, and treatment. The enigmatic phenomenon of glucocorticoid withdrawal syndrome (GWS), due to rapid reduction in cortisol exposure following treatment of CS, is less commonly discussed but also difficult to manage. We highlight the clinical approach to navigating patients from GWS and adrenal insufficiency to full hypothalamic-pituitary-adrenal (HPA) axis recovery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 59 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…The presentation could have also suggested glucocorticoid withdrawal, a state of relative hypocortisolism that might be seen in patients with long-term Cushing’s syndrome who undergo surgery to remove a tumor causing hypercortisolism. 7 Nevertheless, both conditions can be safely treated with hydrocortisone replacement. In retrospect, it appears that osilodrostat 2 mg twice daily plus hydrocortisone (in a block-and-replace strategy 8 ) might have been sufficient, and osilodrostat dose escalation might have not been necessary, despite the patient’s very high 24-hour mUFC at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The presentation could have also suggested glucocorticoid withdrawal, a state of relative hypocortisolism that might be seen in patients with long-term Cushing’s syndrome who undergo surgery to remove a tumor causing hypercortisolism. 7 Nevertheless, both conditions can be safely treated with hydrocortisone replacement. In retrospect, it appears that osilodrostat 2 mg twice daily plus hydrocortisone (in a block-and-replace strategy 8 ) might have been sufficient, and osilodrostat dose escalation might have not been necessary, despite the patient’s very high 24-hour mUFC at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the taper program was adopted to avoid glucocorticoid withdrawal syndrome and unexpected adrenal insufficiency. 14 The cortisol level rebounded almost 2-fold on postoperative days 1 and 2, showing stress tolerance for pituitary surgery and a subsequent robust intrinsic response in these patients. 10,11,33,34 For patients with pituitary adenomas and an intact HPA axis, the literature reports that early postoperative adrenal insufficiency occurs in fewer than 25% of patients and is sustained in fewer than 20% of patients.…”
Section: Discussionmentioning
confidence: 87%
“… 9 , 10 , 11 , 12 There is consensus that patients with insufficient baseline HPA axis function or low serum cortisol levels after surgery for Cushing disease need glucocorticoid supplementation. 13 , 14 However, according to the nonrandomized studies, withholding perioperative glucocorticoids might be safe and not lead to a higher risk of postoperative adrenal insufficiency and could avoid glucocorticoid-related adverse events. 10 , 11 , 15 Two recent randomized clinical trials suggested that perioperative glucocorticoids would be safely withheld under intensive monitoring of postoperative serum cortisol levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond cardiovascular instability and collapse, the symptoms of AI in the perioperative period can be subtle and may be missed due to their similarity to common postoperative complaints including anorexia, fatigue, nausea, vomiting, abdominal pain, muscle cramps, weakness, dizziness, and lethargy [ 62 ]. The clinical team must be aware of GC withdrawal symptoms that may occur in patients on chronic GC on a fast perioperative taper; these patients who may experience AI-type symptoms despite being maintained on supraphysiological GC doses [ 63 , 64 ].…”
Section: Perioperative Symptoms Of Adrenal Insufficiency and Cardiova...mentioning
confidence: 99%